The Mongols and the Armenians (1220-1335) - Dashdondog, Bayarsaikhan (Brill's Inner Asian Library, 2010)
In the thirteenth century, the Armenians of Greater Armenia and of the Armenian Kingdom in Cilicia were invaded by Mongol nomads of the Inner Asian steppe. The ensuing Mongol-Armenian relations were varied. The Greater Armenians became subjects of the Mongol Empire, whereas the Cilician Armenians, by entering into vassalage, became allies and furthered the Mongol conquests. In order to enhance our understanding of this turning point in medieval history, the effects of long distance military raids, missions, diplomacy, collaboration, administrative assistance and confrontation as well as the reasons for invading Greater Armenia and motives for establishing an alliance, are considered.